Gênese dos itabiritos e minérios hipogênicos do Quadrilátero Ferrífero com base em geoquímica e isótopos de ferro e geocronologia de rochas associadas - Monica de Cassia Oliveira Mendes (2015)
The Paleoproterozoic banded iron formations (BIFs) of the Cauê Formation (Minas Supergroup) have a widespread distribution on the Quadrilátero Ferrífero (QF) mineral province. These formations are usually referred as itabirites (metamorphic correspondent of BIFs), hosting high- grade iron ore bodies, which represent great economic importance for the region. Samples of itabirites and ores from four deposits located in the western portion of QF (Usiminas, Pau Branco, Várzea do Lopes e Casa de Pedra) were analyzed for their trace and rare earth elements (REEs) contents and iron isotopic composition. Complementary analyses were performed on itabirites and ores from the eastern high-strain domain, in order to evaluate the influence of the deformational and metamorphic intensities in the their geochemical signature. With the aid of these data, the redox conditions of Minas basin, which resulted in the deposition of the great volume of BIFs, was investigated. Also, the effect of the metamorphism and hydrothermal input on the geochemical and isotopic composition of the itabirites and iron ores was evaluated. The geochemical and isotopic data of the itabirites suggest that the deposition of BIFs occurred in oxidized marine environment, through the precipitation of the dissolved iron, which was previously furnished to the basin by hydrothermal fluids. This points to favorable redox conditions for the deposition of large volumes of BIFs in Minas Basin, indicating a significant influence of the Great Oxidation Event (GOE) in the ancient ocean. Itabirites from the different deformational domains have similar average REE+Y and iron isotope contents, indicating that the metamorphism didnt affect the BIFs geochemical signature in a great extent. The hydrothermal mineralization did not affect in a significant way the geochemical signature of itabirites, once the average REEs compositions of itabirites and ores are similar. However, the isotopic composition is variable among the samples from the different deformational domains, which may be related to the distinct characteristics of the mineralizing fluids in these domains. Geochronological analyses were performed in metassedimentary rocks from the Cercadinho Formation, which is in a superior stratigraphic position in relation to Cauê Formation, and mafic dykes hosted in itabirites and iron ore bodies. The maximum depositional age determined for the Cercadinho Formation (2680 Ma) didnt provide conclusive depositional age for the Cauê Formation, once the inherited zircons are chrono-correlated to the Minas Supergroup basement. The geochronological data obtained for the mafic dykes suggests the occurrence of magmatic pulses associated to two distinct events, being the first related to the Rhyacian Orogenesis, probably chrono-correlated to the hypogenic mineralization event, and the second pulse related to the Statherian Trafrogenesis.